2021
DOI: 10.3390/ijerph18041813
|View full text |Cite
|
Sign up to set email alerts
|

“Stay-at-Home” Lifestyle Effect on Weight Gain during the COVID-19 Outbreak Confinement in China

Abstract: In February 2020, a novel coronavirus (SARS-COV2) broke out in Wuhan city of China. The Chinese government decisively imposed nationwide confinement. This study comprised a structured, online questionnaire, based on 40 items inquiring about socio-demographic information and anthropometric data (reporting weight and height), as well as changes in food intake, physical activity, and sleep during the COVID-19 outbreak. Questionnaires were distributed to residents of Jiangsu and other provinces from 29 March to 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 42 publications
(52 reference statements)
6
86
2
Order By: Relevance
“…The exact amount of caloric increase due to snacking is not provided in the literature. However, a commonly reported theme during COVID-19 self-quarantine is increased snacking frequency [12,15,17,33,36]. For example, crosssectional data from 1097 Poles revealed that 52% of participants admitted to snacking more frequently between meals when compared to before the pandemic [37].…”
Section: Snackingmentioning
confidence: 99%
See 3 more Smart Citations
“…The exact amount of caloric increase due to snacking is not provided in the literature. However, a commonly reported theme during COVID-19 self-quarantine is increased snacking frequency [12,15,17,33,36]. For example, crosssectional data from 1097 Poles revealed that 52% of participants admitted to snacking more frequently between meals when compared to before the pandemic [37].…”
Section: Snackingmentioning
confidence: 99%
“…It seems, however, that controlling total food intake during the COVID-19 pandemic has been problematic. Many studies show that those who gained weight during quarantine reported greater overall food intake [ 12 , 21 , 25 , 28 ]. Additionally, the diet quality of those who gained weight has changed negatively [ 21 , 25 , 32 ].…”
Section: Dietary Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has been reported that people are more likely to become obese due to restrictions on physical activity caused by the COVID-19 pandemic [ 14 ]. Zhu et al reported that during the COVID-19 outbreak people spent most of their time at home, resulting in decreased physical activity and increased food intake, which was closely related to weight gain [ 15 ]. Obesity is a modifiable factor by regulating food consumption as well as physical activity; therefore, dietary intervention holds more weight for preventing/overcoming obesity when people reduce their physical activity, such as during the COVID-19 lockdown.…”
Section: Introductionmentioning
confidence: 99%